Trans-radial approach for coronary angiography in an adult postoperative patient with tetralogy of Fallot with complex anatomy. (14th May 2015) - Rahman, Nasir; Gul, Ibrahim; Ali, Ashique
Abstract : A 42-year-old, postoperative patient with tetralogy of Fallot (TOF) with right-sided aortic arch, presented with heart failure secondary to left ventricular dysfunction, severe valvular regurgitation and residual ventricular septal defect (VSD). After initial stabilisation, he underwent successful coronary angiography through a trans-radial approach followed by aortic valve replacement, pulmonary valve and VSD repair, and was discharged home in stable condition. This case report highlights the trans-radial approach as a feasible option for coronary angiography in postoperative patients with TOF with right-sided aortic arch.